Hard carbon material and preparation method thereof, hard carbon negative pole piece and sodium ion battery
By preparing the hemp rod into a low-cost hard carbon material and applying it to the negative electrode sheet of sodium ion battery, the problem of high cost of hard carbon raw materials is solved and the energy density and circulation performance of the battery are improved.
Patent Information
- Application Number
- CN202411664282.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The existing hard carbon raw materials are costly, limiting the widespread application of sodium ion batteries.
The hemp rod is used as raw material, and a hard carbon precursor is obtained through primary screening, crushing, carbonization, grinding and decomposition. A low-cost hard carbon material is prepared by secondary grinding, primary burning, secondary burning, washing and drying.
The cost of hard carbon materials is reduced, the capacity of hard carbon materials is increased, and the energy density and cycling performance of sodium ion batteries are enhanced.
Smart Images

Figure CN119461328A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to a hard carbon material and a preparation method thereof, a hard carbon negative electrode sheet and a sodium ion battery. Background Art
[0002] The development of sodium-ion batteries is of great significance in alleviating the shortage of lithium resources, reducing dependence on foreign resources, promoting scientific and technological progress and reducing energy costs. With the advancement of technology and the reduction of costs, the application prospects of sodium-ion batteries are becoming more and more broad, and will have a profound impact on many fields such as the electric vehicle market, energy storage market and the power industry. Among them, hard carbon negative electrode materials are important materials for sodium-ion batteries, with the characteristics of high capacity, long cycle life, low cost and high safety. However, hard carbon raw materials are currently expensive and costly. Summary of the invention
[0003] The main purpose of the present invention is to provide a hard carbon material and a preparation method thereof, a hard carbon negative electrode sheet and a sodium ion battery, aiming to reduce the cost of the hard carbon material.
[0004] To achieve the purpose of the present invention, the present invention provides a method for preparing a hard carbon material, the preparation method comprising the following steps:
[0005] The hemp stalks are subjected to primary screening, crushing, carbonization, secondary crushing, grinding and impurity removal in sequence to obtain a hard carbon precursor;
[0006] The hard carbon precursor is subjected to secondary grinding, primary calcination, secondary calcination, washing and drying in sequence to obtain a hard carbon material.
[0007] In one embodiment, the carbonization comprises the following steps:
[0008] The crushed hemp stalks are carbonized in an air atmosphere at a carbonization temperature of 400-700°C, and then cooled to room temperature.
[0009] In one embodiment, the carbonization heating rate is 4-6°C / min, and the heat preservation time is 3-6h.
[0010] In one embodiment, the initial firing comprises the following steps:
[0011] The hard carbon precursor after secondary grinding is initially fired in an inert gas atmosphere at a temperature of 1000-1400°C.
[0012] In one embodiment, the heating rate of the initial calcination is 5-10°C / min, and the holding time is 3-6h.
[0013] In one embodiment, the second calcination comprises the following steps:
[0014] The product after primary firing is subjected to secondary firing at a temperature of 600-1000°C.
[0015] In one embodiment, the heating rate of the secondary calcination is 5-10°C / min, and the holding time is 3-6h.
[0016] The present invention also provides a hard carbon material, wherein the hard carbon is prepared by the method for preparing the hard carbon material as described above.
[0017] The present invention also provides a hard carbon negative electrode plate, which comprises the hard carbon material as described above.
[0018] The present invention also provides a sodium ion battery, which comprises the hard carbon negative electrode sheet, positive electrode sheet and diaphragm as described above, wherein the diaphragm is arranged between the hard carbon negative electrode sheet and the positive electrode sheet.
[0019] The preparation method of the hard carbon material provided by the present invention uses hemp stalks as raw materials, firstly, the hemp stalks are subjected to primary screening, crushing, carbonization, secondary crushing, grinding and impurity removal in sequence to obtain a hard carbon precursor; then the hard carbon precursor is subjected to secondary grinding, primary calcination, secondary calcination, washing and drying in sequence to obtain the hard carbon material. Therefore, the preparation operation is relatively simple, and the hemp stalks are waste after processing linen cloth, and the price is relatively low, which can reduce the cost of the hard carbon material, and can be obtained from linen cloth manufacturers on a large scale, which is convenient for large-scale collection. The hard carbon material using hemp stalks as raw materials is applied to the negative electrode sheet of a sodium ion battery. Since the hemp stalks have the characteristics of being strong and loose, the gram capacity of the obtained hard carbon material is relatively high, which is beneficial to improving the energy density of the sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0021] Figure 1 Schematic diagram for comparing the charge and discharge curves of Example 1, Example 2 and Example 3 of the present invention.
[0022] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0023] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.
[0024] To make the purpose, technical scheme and advantages of the embodiment of the present invention clearer, the technical scheme in the embodiment of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiment, it is carried out according to the normal conditions or the conditions recommended by the manufacturer. If the reagents or instruments used do not specify the manufacturer, they are all conventional products that can be purchased commercially. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes, taking "A and / or B" as an example, including scheme A, or scheme B, or schemes that A and B meet at the same time. In addition, the technical schemes between the various embodiments can be combined with each other, but must be based on the ability of ordinary technicians in the field to achieve. When the combination of technical solutions is contradictory or cannot be achieved, it should be considered that the combination of such technical solutions does not exist, and is not within the scope of protection required by the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the scope of protection of the present invention.
[0025] In view of the current technical problem that hard carbon raw materials are expensive and costly, the present invention provides a method for preparing a hard carbon material using hemp stalks as raw materials, aiming to reduce the cost of the hard carbon material.
[0026] Hemp stalks are the peeled stems of hemp and other hemp varieties. The stems are slender and strong, and the carbon products are rich in pores. Hemp stalks are waste after processing linen cloth, with low value and easy to collect on a large scale. Hemp stalks are strong and loose, making them ideal materials for making hard carbon. They have a high hard carbon yield, and their loose and porous properties are also conducive to the regulation of the later pore structure and the increase of sodium storage sites.
[0027] The method for preparing the hard carbon material provided by the present invention comprises the following steps:
[0028] Step S1, sequentially performing primary screening, crushing, carbonization, secondary crushing, grinding and impurity removal on the hemp stalks to obtain a hard carbon precursor.
[0029] The specific steps of the initial screening are as follows: placing the hemp stalks raw materials on a vibrating screening conveyor for preliminary screening to remove other substances mixed in the hemp stalks, such as larger particles of impurities such as soil and stones attached to the surface of the hemp stalks.
[0030] The specific crushing is as follows: after the initial screening is completed, the hemp stalks are conveyed to the wood crusher for crushing through a vibrating screening conveyor. The crushed hemp stalks are smaller particles or powder. The size of the crushed particles can be adjusted according to specific experiments or production needs. The smaller the particles, the more complete the reaction in the subsequent carbonization process. Optionally, the particle size of the crushed hemp stalk particles is 0.1-1mm (such as 0.1mm, 0.3mm, 0.5mm, 0.8mm, 1mm and the interval between any two end points). Particles of this particle size are conducive to uniform heating and carbonization reaction.
[0031] The carbonization is specifically as follows: the crushed hemp stalks are carbonized in an air atmosphere, and naturally cooled to room temperature after the carbonization is completed, wherein the heating rate of the carbonization process is 4-6°C / min (such as 4°C / min, 5°C / min, 6°C / min and any interval between the two end points), the carbonization temperature is 400-700°C (such as 400°C, 500°C, 600°C, 700°C and any interval between the two end points), and the heat preservation time is 3-6h (such as 3h, 4h, 5h, 6h and any interval between the two end points). The above carbonization conditions can fully decompose and polycondense the organic components in the hemp stalks to obtain carbonized products.
[0032] The secondary crushing and grinding specifically includes: performing secondary crushing and grinding on the cooled carbonized product, and the particle size of the ground particles is 50-100 mesh (such as 50 mesh, 60 mesh, 70 mesh, 80 mesh, 90 mesh, 100 mesh and the interval value between any two end point values).
[0033] The impurity removal is specifically as follows: washing the carbonized product with water to remove dust or small particles that are not completely carbonized on the surface of the carbonized product.
[0034] After removing impurities, a hard carbon precursor with higher purity can be obtained.
[0035] Step S2, subjecting the hard carbon precursor obtained in step S1 to secondary grinding, primary calcination, secondary calcination, washing and drying in sequence to obtain a hard carbon material.
[0036] The secondary grinding specifically includes: secondary grinding of the hard carbon precursor, and the particle size D50 after the secondary grinding is 3-9 μm (such as 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm and an interval value between any two end points).
[0037] The role of initial firing is to initially form the basic structure of hard carbon. When the hard carbon precursor is initially fired, the organic components of cellulose, hemicellulose and lignin are further decomposed, releasing small molecular gases, leaving behind a basic carbon framework.
[0038] The initial firing is specifically as follows: the hard carbon precursor after secondary grinding is placed in a furnace with an inert gas for initial firing, the heating rate of the initial firing process is 5-10°C / min (such as 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min and the interval between any two end points), the initial firing temperature is 1000-1400°C (such as 1000°C, 1100°C, 1200°C, 1300°C, 1400°C and the interval between any two end points), and the holding time is 3-6h (such as 3h, 4h, 5h, 6h and the interval between any two end points). The above initial firing conditions can not only fully decompose the organic components in the hard carbon precursor, but also prevent the structure from collapsing or excessive graphitization due to excessive temperature.
[0039] In some embodiments, the inert gas includes one of nitrogen, argon, and a hydrogen-argon mixture, wherein the volume ratio of hydrogen to argon in the hydrogen-argon mixture is 5:95. The initial calcination is carried out in an inert gas atmosphere, which can effectively prevent the hard carbon precursor from being oxidized by oxygen and affecting the yield and purity of the hard carbon material.
[0040] The role of the second firing is to further optimize the structure of hard carbon. Through the second firing, the pore structure of hard carbon can be adjusted, the crystallinity can be improved, impurities and defects can be reduced, etc. After the second firing, the density of hard carbon will increase, and its hardness and strength will also increase accordingly. After the hard carbon material after the second firing is applied to the negative electrode of the sodium ion battery, it is conducive to the embedding and extraction of sodium ions, and improves the electrochemical performance of the sodium ion battery. At the same time, the hard carbon structure after the second firing is more stable, and its structural integrity can be better maintained during the charge and discharge cycle, so the cycle performance of the sodium ion battery will also be significantly improved.
[0041] The second firing is specifically as follows: the product after the initial firing is subjected to the second firing, the temperature of the second firing is 600-1000°C (such as 600°C, 700°C, 800°C, 900°C, 1000°C and the interval between any two end points), the heating rate of the second firing is 5-10°C / min (such as 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min and the interval between any two end points), and the insulation time is 3-6h (such as 3h, 4h, 5h, 6h and the interval between any two end points). The above-mentioned second firing conditions can better regulate the pore structure of the hard carbon and make the hard carbon structure more stable.
[0042] The washing process specifically includes: pickling the product after the second calcination to remove impurities (such as metal impurities) therein. At the same time, pickling also etches the surface of the hard carbon material to a certain extent, increasing its specific surface area and porosity, which is beneficial to the subsequent transmission and storage of sodium ions. The pickling solution used for pickling can be hydrochloric acid or sulfuric acid with a mass concentration of 10%-20%.
[0043] The purpose of drying is to remove the acid and water remaining after pickling to prevent them from affecting the performance of the hard carbon material. The drying temperature can be selected to be 80-120°C (such as 80°C, 90°C, 100°C, 110°C, 120°C and any interval between the two end points), and the drying time can be selected to be 8-12h (such as 8h, 9h, 10h, 11h, 12h and any interval between the two end points).
[0044] The preparation method of the hard carbon material provided by the present invention uses hemp stalks as raw materials, firstly, the hemp stalks are subjected to primary screening, crushing, carbonization, secondary crushing, grinding and impurity removal in sequence to obtain a hard carbon precursor; then the hard carbon precursor is subjected to secondary grinding, primary calcination, secondary calcination, washing and drying in sequence to obtain the hard carbon material. Therefore, the preparation operation is relatively simple, and the hemp stalks are waste after processing linen cloth, and the price is relatively low, which can reduce the cost of the hard carbon material, and can be obtained from linen cloth manufacturers on a large scale, which is convenient for large-scale collection. The hard carbon material using hemp stalks as raw materials is applied to the negative electrode sheet of a sodium ion battery. Since the hemp stalks have the characteristics of being strong and loose, the gram capacity of the obtained hard carbon material is relatively high, which is beneficial to improving the energy density of the sodium ion battery.
[0045] The present invention also provides a hard carbon material, which is prepared by the hard carbon material preparation method described in the above embodiment.
[0046] The present invention also provides a hard carbon negative electrode plate, which comprises the hard carbon material mentioned above.
[0047] The hard carbon negative electrode plate of the present invention can be prepared by the following steps: (a) preparing hard carbon negative electrode slurry, mixing hard carbon material, conductive agent and binder in a mass ratio of (70-90): (3-10): (3-7) to obtain a dry powder mixture, then adding solvent water, stirring and mixing to obtain negative electrode slurry, the solid content of the negative electrode slurry is 40wt%-70wt% (such as 40wt%, 50wt%, 60wt%, 70wt% and the interval between any two end points). (b) uniformly coating the negative electrode slurry on the surface of aluminum foil, vacuum drying, cold pressing and cutting to obtain a hard carbon negative electrode plate, the shape of the hard carbon negative electrode plate can be round, square or other reasonable shapes.
[0048] In some embodiments, the conductive agent includes, but is not limited to, carbon black (such as Super P, Ketjen Black, etc.), conductive graphite, carbon nanotubes, and graphene.
[0049] In some embodiments, the binder includes, but is not limited to, sodium carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), polyacrylic acid (PAA).
[0050] The present invention also provides a sodium ion battery, which comprises the hard carbon negative electrode sheet, the positive electrode sheet and the separator as described above, wherein the separator is located between the hard carbon negative electrode sheet and the positive electrode sheet, the positive electrode sheet comprises a positive electrode collector (such as aluminum foil) and a positive electrode active material coated on the surface of the positive electrode collector, the positive electrode active material comprises a layered transition metal oxide, a polyanionic compound, and a Prussian blue compound; the separator comprises but is not limited to PP, PE, PP / PE, PP / PE / PP separators, and ceramic separators.
[0051] Here, the sodium ion battery also includes an electrolyte, which is composed of a solvent, a sodium salt, an additive, etc. The sodium salt includes but is not limited to sodium perchlorate, sodium trifluoromethanesulfonate, and sodium hexafluorophosphate; the solvent includes but is not limited to a mixture of one or more of dimethyl carbonate, propylene carbonate, ethylene carbonate, and ethylene glycol dimethyl ether.
[0052] The hard carbon material and preparation method thereof, hard carbon negative electrode sheet and sodium ion battery of the present invention are described in detail below through specific examples.
[0053] Example 1
[0054] This embodiment provides a method for preparing a hard carbon material, comprising the following steps:
[0055] (1) Place the hemp stalk raw material on a vibrating screening conveyor for preliminary screening to remove other substances mixed in the hemp stalk.
[0056] (2) The hemp stalks after preliminary screening are conveyed to a wood crusher for crushing, and the particle size of the crushed hemp stalk particles is 0.5 mm.
[0057] (3) The crushed hemp stalks are carbonized in an air atmosphere at a heating rate of 5°C / min, a carbonization temperature of 500°C, and a holding time of 3 h. After the carbonization is completed, the stalks are naturally cooled to room temperature.
[0058] (4) The cooled carbonized product is crushed and ground for the second time, and the particle size of the ground particles is 80 meshes, and then washed with water to remove impurities to obtain a hard carbon precursor.
[0059] (5) The hard carbon precursor is subjected to secondary grinding, and the particle size D50 after the secondary grinding is 6 μm.
[0060] (6) The hard carbon precursor after secondary grinding is placed in a furnace filled with inert gas for initial calcination. The heating rate of the initial calcination process is 8°C / min, the initial calcination temperature is 1200°C, and the holding time is 4h.
[0061] (7) The product after primary calcination is subjected to secondary calcination at a temperature of 800°C, a heating rate of 6°C / min, and a holding time of 5 h.
[0062] (8) The product after the second calcination is acid-washed and dried to obtain a hard carbon material.
[0063] This embodiment also provides a method for assembling a sodium ion battery, which specifically includes the following steps:
[0064] 1. Preparation of hard carbon negative electrode sheets: First, the hard carbon material, conductive carbon black, sodium carboxymethyl cellulose and styrene-butadiene rubber prepared above are mixed in a mass ratio of 90:5:2:3, and then deionized water is added and stirred to obtain a negative electrode slurry with a solid content of 40wt%. The negative electrode slurry is then evenly coated on the surface of the aluminum foil. After vacuum drying, cold pressing and cutting, a disc-shaped hard carbon negative electrode sheet with a diameter of 12mm is obtained.
[0065] 2. Preparation of positive electrode plate: Polyanionic compound material is used as the material of the positive electrode plate.
[0066] 3. Diaphragm: PP diaphragm is used.
[0067] 4. Electrolyte: Sodium hexafluorophosphate electrolyte is used.
[0068] 5. Assemble the battery: Assemble the hard carbon negative electrode sheet, positive electrode sheet, diaphragm and separator prepared above into a 2025 button battery.
[0069] It should be noted that the specific preparation of the positive electrode plate, the specific components of the electrolyte, and the specific assembly operation of the 2025 button battery can refer to the existing technology and will not be described in detail here.
[0070] The 2025 button cell assembled in this embodiment was subjected to a charge and discharge test, and its charge and discharge curve is as follows: Figure 1 Its capacity data is shown in Table 1.
[0071] Example 2
[0072] The difference between this embodiment and embodiment 1 is that the initial firing temperature in step (6) is 1100°C, and the other operations are the same as those in embodiment 1. The charge and discharge curves of the 2025 button-type battery assembled in embodiment 2 are also as shown in FIG. Figure 1 Its capacity data is shown in Table 1.
[0073] Example 3
[0074] The difference between this embodiment and embodiment 1 is that the second calcination temperature in step (7) is 700°C, and the other operations are the same as those in embodiment 1. The charge and discharge curves of the 2025 button cell assembled in embodiment 2 are also as shown in FIG. Figure 1 Its capacity data is shown in Table 1.
[0075] from Figure 1 It can be seen that compared with Example 1, after the initial firing temperature of Example 2 is lowered, the charging platform of its charge-discharge curve is slightly higher, indicating that the polarization of the battery is slightly larger; compared with Example 1, after the secondary firing temperature of Example 3 is lowered, the slope area of its charge-discharge curve is further to the left, its dynamics is slightly worse, and the specific capacity is relatively reduced. It can be seen that the initial firing temperature mainly affects the polarization of the battery, and the secondary firing temperature mainly affects the specific capacity of the battery.
[0076] Example 4
[0077] The difference between this embodiment and embodiment 1 is that the initial firing temperature in step (6) is 1400° C., and the other operations are the same as those in embodiment 1. The capacity data of the 2025 button-type battery assembled in embodiment 4 is shown in Table 1.
[0078] Example 5
[0079] The difference between this embodiment and embodiment 1 is that the second calcination temperature in step (7) is 900° C., and the other operations are the same as those in embodiment 1. The capacity data of the 2025 button-type battery assembled in embodiment 5 is shown in Table 1.
[0080] Table 1 Capacity data of 2025 button batteries assembled in Examples 1-5
[0081] Serial number Discharge specific capacity (mAh / g) Charge specific capacity (mAh / g) First efficiency (%) Example 1 380.7 344.5 90.49 Example 2 383.6 346.8 90.41 Example 3 375.1 340.5 90.78 Example 4 373.7 337.6 90.35 Example 5 372.5 336.9 90.44
[0082] It can be seen from the data in Table 1 that when preparing hard carbon materials in Examples 1-5 of the present invention, by reasonably regulating the initial sintering temperature and the secondary sintering temperature in the preparation process, the hard carbon materials prepared are used to prepare hard carbon negative electrode sheets and assembled to obtain 2025 button batteries. The discharge specific capacity of the obtained batteries can reach more than 372.5 mAh / g, and the charging specific capacity can reach more than 336.9 mAh / g. The gram capacity is relatively high, which is beneficial to improving the energy density of the battery, and the first efficiency reaches more than 90%.
[0083] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or system including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or system. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or system including the element.
[0084] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent articles or equivalent process changes made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a hard carbon material, characterized in that: The preparation method comprises the following steps: The hemp stalks are subjected to primary screening, crushing, carbonization, secondary crushing, grinding and impurity removal in sequence to obtain a hard carbon precursor; The hard carbon precursor is subjected to secondary grinding, primary calcination, secondary calcination, washing and drying in sequence to obtain a hard carbon material.
2. The method for preparing a hard carbon material according to claim 1, characterized in that: The carbonization comprises the following steps: The crushed hemp stalks are carbonized in an air atmosphere at a carbonization temperature of 400-700°C, and then cooled to room temperature.
3. The method for preparing a hard carbon material according to claim 2, characterized in that: The carbonization heating rate is 4-6°C / min, and the heat preservation time is 3-6h.
4. The method for preparing a hard carbon material according to claim 1, characterized in that: The initial firing comprises the following steps: The hard carbon precursor after secondary grinding is initially fired in an inert gas atmosphere at a temperature of 1000-1400°C.
5. The method for preparing a hard carbon material according to claim 4, characterized in that: The heating rate of the initial calcination is 5-10°C / min, and the heat preservation time is 3-6h.
6. The method for preparing a hard carbon material according to any one of claims 1 to 5, characterized in that: The second calcination comprises the following steps: The product after primary firing is subjected to secondary firing at a temperature of 600-1000°C.
7. The method for preparing a hard carbon material according to claim 6, characterized in that: The heating rate of the second calcination is 5-10°C / min, and the insulation time is 3-6h.
8. A hard carbon material, characterized in that: The hard carbon material is prepared by the method for preparing a hard carbon material according to any one of claims 1 to 7.
9. A hard carbon negative electrode plate, characterized in that: The hard carbon negative electrode plate comprises the hard carbon material as claimed in claim 8.
10. A sodium ion battery, characterized in that: The sodium ion battery comprises the hard carbon negative electrode sheet, the positive electrode sheet and the separator as claimed in claim 9, wherein the separator is arranged between the hard carbon negative electrode sheet and the positive electrode sheet.
Citation Information
Patent Citations
Mesh-shaped mesoporous hard carbon material as well as preparation method and application thereof in lithium ion battery
CN108321392A
Preparation method and application of hard carbon taking cotton and hemp biomass as raw material
CN118047370A
Cited By
Negative electrode active material and preparation method therefor, negative electrode sheet, battery, and electric device
WO2026189044A1